Performance Analysis in E-Government Management through Pusat Informasi & Koordinasi Covid-19 Jawa Barat (PIKOBAR) Aplication - N Karniawati; S O Sansini (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to examine the Performance analysis in e-Government management through Pusat Informasi & Koordinasi Covid-19 Jawa Barat (PIKOBAR). PIKOBAR is an information service innovation related to the Covid-19 pandemic in West Java. However, this application still has problems in tern of providing information especially on application features. So that the delivery of information to the public regarding the Covid-19 pandemic is still an obstacle. This study uses a descriptive method with a qualitative approach. The results show that the performance aspect still has obstacles in product performance and response time